1998
DOI: 10.1111/j.1547-5069.1998.tb01266.x
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Gender Differences in Quality of life Following Kidney Transplantation

Abstract: Although transplantation dramatically improves QoL, some segments of the patient population, namely African-Americans and women, do not benefit to the same extent as others. Nurses need to recognize sociocultural differences in patients and how these differences affect care requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
42
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 23 publications
7
42
3
Order By: Relevance
“…Meier-Kriesche et al [34], in a study using data from the US Transplant Scientific Registry and USRDS (1988 and 1997), concluded that female recipients had 10% increased chance of acute rejection (p < 0.001) during the first 6 months after transplantation; however, female recipients had 10% less chronic allograft failure compared to male recipients (p < 0.001). Other investigators found similar results [35,36,37]. …”
Section: Literature Reviewsupporting
confidence: 80%
See 1 more Smart Citation
“…Meier-Kriesche et al [34], in a study using data from the US Transplant Scientific Registry and USRDS (1988 and 1997), concluded that female recipients had 10% increased chance of acute rejection (p < 0.001) during the first 6 months after transplantation; however, female recipients had 10% less chronic allograft failure compared to male recipients (p < 0.001). Other investigators found similar results [35,36,37]. …”
Section: Literature Reviewsupporting
confidence: 80%
“…This may explain why women often record a consistently lower quality of life than their male counterparts, particularly with regard to poor self-esteem and body image both before and after transplant [35, 48]. It remains to be seen if these aspects of behavior influence health care providers to list patients for a kidney transplant.…”
Section: Discussionmentioning
confidence: 99%
“…However, this difference, although statistically significant, is not considered to be clinically meaningful [16]. A difference of 2-3 points in the QLI scores has been associated with significant improvement in overall quality of life in studies assessing change in quality of life [23,24]. It is worth noting that previous studies differ from the present study with regard to the definition of CAM, with the present study specifically assessing the use of dietary supplements.…”
Section: Discussionmentioning
confidence: 68%
“…This report discounted the poor HLA matching for African American patients suggested in earlier reports (40,41), and concluded that non-HLA mechanisms must contribute to the poor renal transplant outcomes in African American patients. The higher rates of acute rejection and graft failure in African American patients result in a poorer quality of life for African American transplant patients (42). These observations about African American patients and poor renal transplant outcomes have now been extended to pediatric (43) and adult liver transplantation (44), and to pediatric heart transplantation (45).…”
Section: Discussionmentioning
confidence: 96%